Accuracy of polyp localization at colonoscopy - O’Connor, Sam A.; Hewett, David G.; Watson, Marcus O.; Kendall, Bradley J.; Hourigan, Luke F.; Holtmann, Gerald (Endoscopy International Open, 2016)
Background and study aims: Accurate documentation of lesion localization at the time of colonoscopic polypectomy is important for future surveillance, management of complications such as delayed bleeding, and for guiding surgical resection. We aimed to assess the accuracy of endoscopic localization of polyps during colonoscopy and examine variables that may influence this accuracy.Patients and methods: We conducted a prospective observational study in consecutive patients presenting for elective, outpatient colonoscopy. All procedures were performed by Australian certified colonoscopists. The endoscopic location of each polyp was reported by the colonoscopist at the time of resection and prospectively recorded. Magnetic endoscope imaging was used to determine polyp location, and colonoscopists were blinded to this image. Three experienced colonoscopists, blinded to the endoscopist’s assessment of polyp location, independently scored the magnetic endoscope images to obtain a reference standard for polyp location (Cronbach alpha 0.98). The accuracy of colonoscopist polyp localization using this reference standard was assessed, and colonoscopist, procedural and patient variables affecting accuracy were evaluated.Results: A total of 155 patients were enrolled and 282 polyps were resected in 95 patients by 14 colonoscopists. The overall accuracy of polyp localization was 85 % (95 % confidence interval, CI; 60 – 96 %). Accuracy varied significantly (P < 0.001) by colonic segment: caecum 100 %, ascending 77 % (CI;65 – 90), transverse 84 % (CI;75 – 92), descending 56 % (CI;32 – 81), sigmoid 88 % (CI;79 – 97), rectum 96 % (CI;90 – 101). There were significant differences in accuracy between colonoscopists (P < 0.001), and colonoscopist experience was a significant independent predictor of accuracy (OR 3.5, P = 0.028) after adjustment for patient and procedural variables.Conclusions: Accuracy of localization of polyps is imprecise and affected by position within the colon and colonoscopist, including their level of experience. Magnetic endoscope imaging may improve the localization of lesions during colonoscopy.